2022
DOI: 10.1021/acs.joc.2c00476
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Free Annulation of Acylethynylpyrroles with 1-Pyrrolines: A Straightforward Access to Tetrahydrodipyrrolo[1,2-a:1′,2′-c]imidazoles

Abstract: Acylethynylpyrroles undergo facile (rt, MeCN or MeOH, 24–72 h) catalyst-free annulation with 1-pyrrolines to afford acylmethylenetetrahydrodipyrrolo­[1,2-a:1′,2′-c]­imidazoles in up to 93% yield and 90% E-stereoselectivity of the olefin moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 28 publications
2
25
1
Order By: Relevance
“…The above experimental data evidence that, like in the previous work [ 23 ], the nucleophilic attack of the pyrroline nitrogen at the triple bond plays a key role here. The proton transfer from the pyrrole NH moiety to the vinyl carbanionic center in intermediate A delivers pyrrolate-centered intermediate B .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The above experimental data evidence that, like in the previous work [ 23 ], the nucleophilic attack of the pyrroline nitrogen at the triple bond plays a key role here. The proton transfer from the pyrrole NH moiety to the vinyl carbanionic center in intermediate A delivers pyrrolate-centered intermediate B .…”
Section: Resultssupporting
confidence: 88%
“…Recently [ 23 ], we have serendipitously found that as a convenient platform for the construction of a dipyrrolo[1,2- a :1′,2′- c ]imidazole core, acylethynylpyrroles, readily available from the Al 2 O 3 -promoted cross-coupling of acylbromoacetylenes with pyrroles [ 24 ], can be successfully employed. The similar condensed heterocyclic systems are of high medicinal relevance as they are the principal structural units of compounds with antiviral properties [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A possible transformation of D′ also includes reversible pyrrolo[1,2‐ c ]imidazole system J formation by intramolecular pyrrolyl anion attack to benzimidazolyl carbon through TS D′–J . Similar [3+2]‐cycloaddition of acylpyrrolylacetylenes to the C=N bond in 1‐pyrrolines was recently observed [22] . But in this case the magnitude of TS D′–J barrier is lower compared with that of TS D′–E .…”
Section: Resultssupporting
confidence: 72%
“…Similar [3 + 2]cycloaddition of acylpyrrolylacetylenes to the C=N bond in 1pyrrolines was recently observed. [22] But in this case the magnitude of TS D'-J barrier is lower compared with that of…”
Section: Scheme 2 Synthesis Of Benzodiazocinone/pyrrole Ensemblesmentioning
confidence: 78%
“…17 Second, these compounds proved to be efficient building blocks for a variety of pyrrole heterocyclic ensembles. 18 Third, such cyclization may open a route to hitherto unknown pyrrolo[1,2- c ]oxazoles free of exocyclic carbonyl groups and functionalized by acylmethylidene substituents, which promise rich chemical modifications.…”
Section: Introductionmentioning
confidence: 99%